P11.09 Sti prevention in public health services for transgender women in guatemala. (13th September 2015) - Mendizabal-Burastero, R; Galindo-Arandi, C; Loya-Montiel, I; Garcia, J; Morales-Miranda, S
Abstract : Introduction: Transgender women (TG) have the highest HIV prevalence in Guatemala (23.9%). Since 2007, the STI Sentinel Surveillance and Control (VICITS) strategy has provided STI diagnosis and treatment, behavioural change interventions and condoms to key populations in coordination with the Ministry of Health. We present key biological and behavioural characteristics of TG who attended VICITS clinics in Guatemala between 2007 and 2014. Methods: TG ≥18 years old (yo), who had sex with a man in the last year and attended one of four VICITS clinics in Guatemala were included in the analysis. HIV and syphilis infection were diagnosed according to national guidelines. Sociodemographic data, risk behaviour, and biological data were collected. Data analysis was conducted in Stata 11.0. Results: A total of 151 TG sought care at least once during 2007–2014 and 366 consultations were provided. Median age was 27 yo (IQR 23–34), 76.3% had secondary education or more, 77.7% reported sex work in the last year (75% for more than one year), 40.4% reported drug use at least once in lifetime with half of them reporting active use in the last 30 days - cocaine was the most common drug. Condom use in the last sexual relationship was 85.4%, 89% of the TG reported receptive anal sex and 88.8% oral sex in the last 30 days. Approximately 7.2% had a previous HIV diagnosis and 4.2% were newly diagnosed for a total HIV prevalence of 11%. Of those tested for syphilis, 3.9% had active syphilis infection. Conclusion: We found high HIV and active syphilis prevalence among TG, suggesting that additional efforts and strategies for prevention among this group are needed. Due to the high proportion of receptive anal sex reported, surveillance of anal STI should be prioritised and conducted to provide appropriate and timely data to control the epidemic among key populations. Disclosure of interest statement: We declare that we have no conflicts of interest.